Android-Based Monitoring System for Water Usage Observation and Control - Muhammad Wahyu Alfaris; Lukmanul Khakim; Arif Rakhman; Arfan Haqiqi Sulasmoro (Indonesian Journal of Electronics and Computer Technology, 2026)
Water is an essential resource that sustains human life, particularly in fulfilling daily domestic needs. However, the availability of clean water in various regions around the world has been declining significantly, which is not proportional to the continuously increasing population growth. This condition necessitates efforts in managing and utilizing water resources efficiently and sustainably. One applicable approach is optimizing water usage in storage tanks through an integrated monitoring and control system. This study aims to design and implement an Android-based monitoring and control system for water usage that is capable of providing real-time information to users. The system is developed by utilizing microcontroller technology and mobile platforms to enhance the effectiveness of water management. The components used in the system development include an Android smartphone as the user interface, Arduino as the main controller, and software tools such as Arduino IDE, Visual Studio Code, and Android Studio. In addition, Firebase is employed as a database and an online data communication medium. The expected outcome of this study is the development of a system that can improve user awareness in conserving water and support more efficient and measurable water resource management.